A study to assess the pulmonary functions in a cement ware house workers near railway station, Nishatpura, Bhopal - Rathore, Bhavishya; Neelkanth, Namita; Toppo, Manju (International Journal Of Community Medicine And Public Health, 2017)
Background: It is unfortunate enough that cement industry workers despite of so many awareness campaigns, unable to seek protection against dust of cement and thus bound to face respiratory problems. In developing countries no legitimate bindings regarding protection of such workers though cement industry is one of the largest industries. Methods: Non probability sampling done in which cases taken from cement workers and control taken from nearby residents matched for age gender and smoking status of participants. Results: When studied for the restrictive and obstructive respiratory problems it was found 2.82 times and 4.71 times higher in cases respectively. When cases studied for duration of working against disease developed, it was found that 61.81% developed obstructive pulmonary disorder and proportion increased from 23.63% to 30.80 as the work span increased from 0-5 years to 5-15 years respectively. When it has been observed for restrictive pulmonary disorder, it has been increased from 3.6% to 5.4%. Conclusions: It has been observed that workers have either obstructive pulmonary dysfunction or normal pulmonary functions and on increasing the duration, number of workers with restrictive pulmonary function increases proportionately.